The Influence of Internship and Student Motivation on Agribusiness Entrepreneurship Interests of MA Darul Fallah Ciampea Students - Kuraesin, Ecin; Aramli, Riri; Nugrahaningsih, Hartanti; Muniroh, Leny (prodima@fe.uika-bogor.ac.id, 2025)
This study aims to determine the effect of internships and student motivation on interest in agribusiness entrepreneurship among students of Madrasah Aliyah Darul Fallah Ciampea, Bogor. The study used a descriptive quantitative approach with a questionnaire as an instrument, involving 31 respondents. Data analysis was carried out using SPSS 26 with validity, reliability, correlation, and multiple linear regression tests. The test results showed that internships had a positive and significant effect on interest in agribusiness entrepreneurship (H1 was accepted), as well as student motivation (H2 was accepted). Simultaneously, these two variables also had a positive and significant effect on interest in agribusiness entrepreneurship (H3 was accepted). The coefficient of determination value of 70.6% indicates that internships and student motivation contribute greatly to interest in agribusiness entrepreneurship, while 29.4% is influenced by other variables outside this study. The conclusion shows that there is a very strong, positive, and significant relationship between internships, motivation, and interest in agribusiness entrepreneurship.